2018
DOI: 10.1200/jgo.18.95600
|View full text |Cite
|
Sign up to set email alerts
|

Summary Report of a Successful Policy/Advocacy Campaign by Breast Care International in Ghana

Abstract: Background and context: Breast cancer is rapidly becoming a growing public health problem in sub-Saharan Africa and has the highest mortality among women. Research has demonstrated that African women are diagnosed with breast cancer 10 to 15 years earlier than their counterparts in higher-income countries. According to GLOBOCAN, in 2012 it was estimated that 2260 women are diagnosed with breast cancer and out of it 1102 died in Ghana. Breast cancer accounts for 15% of all malignancies in Ghana and it is estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Though the relevant signs and symptoms differ, successful interventions targeting adults with cancer in LMICs can potentially be tailored to LMIC pediatric populations. Use of social media (Facebook, Twitter), 29,30 awareness through social events, 31 policy advocacy campaigns reaching out to organized groups within the community, 32 national social marketing compaigns, 33 and an increase in incidence of early stage disease (3.3/100 000 vs 0.7/100 000 person-years; P = .048) in intervention areas. 35 Other studies have also demonstrated the efficacy of training community health workers in the early detection and referral of breast and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the relevant signs and symptoms differ, successful interventions targeting adults with cancer in LMICs can potentially be tailored to LMIC pediatric populations. Use of social media (Facebook, Twitter), 29,30 awareness through social events, 31 policy advocacy campaigns reaching out to organized groups within the community, 32 national social marketing compaigns, 33 and an increase in incidence of early stage disease (3.3/100 000 vs 0.7/100 000 person-years; P = .048) in intervention areas. 35 Other studies have also demonstrated the efficacy of training community health workers in the early detection and referral of breast and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Though the relevant signs and symptoms differ, successful interventions targeting adults with cancer in LMICs can potentially be tailored to LMIC pediatric populations. Use of social media (Facebook, Twitter), 29,30 awareness through social events, 31 policy advocacy campaigns reaching out to organized groups within the community, 32 national social marketing compaigns, 33 and the use of technology such as tablet‐based interactive education 34 have all been shown to be both feasible and effective in LMIC settings in increasing uptake of breast, colon, and prostate cancer screening. Using a cluster randomized controlled trial design, Pace et al reported on the efficacy of a training program for health workers in Rwanda targeting the early diagnosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%